2008
DOI: 10.1063/1.3039809
|View full text |Cite
|
Sign up to set email alerts
|

Improved endurance behavior of resistive switching in (Ba,Sr)TiO3 thin films with W top electrode

Abstract: We compared the resistive switching performance of barium strontium titanate (BST) thin films with tungsten (W) and platinum (Pt) top electrodes, respectively. The yield, endurance, and reliability were strongly improved for the samples with W top electrode. Whereas the samples with Pt top electrode show a fast drop in the resistance for both high and low resistance states, the devices with W top electrode can be switched for 104 times without any obvious degradation. We attribute the improved switching perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 21 publications
3
80
0
Order By: Relevance
“…Since we observed only bipolar switching in epitaxial BST films as reported before 9 and no unipolar switching in epitaxial perovskite systems have been observed so far, grain boundaries have to play a crucial role for the realization of the unipolar switching mode. The importance of grain boundaries in terms of unipolar switching was already demonstrated by Park et al 17 Lee et al 18 also observed that the epitaxial binary oxide NiO shows bipolar switching while the polycrystalline NiO shows unipolar switching.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Since we observed only bipolar switching in epitaxial BST films as reported before 9 and no unipolar switching in epitaxial perovskite systems have been observed so far, grain boundaries have to play a crucial role for the realization of the unipolar switching mode. The importance of grain boundaries in terms of unipolar switching was already demonstrated by Park et al 17 Lee et al 18 also observed that the epitaxial binary oxide NiO shows bipolar switching while the polycrystalline NiO shows unipolar switching.…”
Section: Resultsmentioning
confidence: 64%
“…However, the R off / R on is much smaller compared to our epitaxial BST thin film devices. 9 If the current compliance is increased to 20 mA, another forming occurs at positive branch ͑not shown here͒ and the device is transformed to a better conducting and linear behavior, as can be seen in Fig. 1͑c͒, this linear branch acts as LRS of a unipolar switching state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is strongly confirmed that oxygen ions are able to move in the TiO 2−x amorphous active layer by a strong external electric field, as reported by other groups. 12,17 Based on above results, the bipolar switching mechanisms of our Al/ TiO 2 / Al devices can be described schematically in Fig. 4͑c͒.…”
Section: Microscopic Origin Of Bipolar Resistive Switching Of Nanoscamentioning
confidence: 99%
“…This model can also be used for the RS systems with other metal electrodes such as Al, W, Ta, where AlO x , WO x and TaO x form at the metal/film interface region. [50][51][52][53] The interfacial layer formation is not only related to the Gibbs free energy of oxide formation of metal electrodes, but also with the electrode preparation techniques. For instance, Shang et al [54] and Fujimoto et al [55] used silver paste as the top electrode and found that the Ag(paste)/La 0.7 Ca 0.3 MnO 3 interface exhibit an obvious I-V hysteresis and a stable RS property.…”
Section: Interfacial-layer-type Rsmentioning
confidence: 99%